5x53-{4x[5+(a-2)x7]:3}x6=1
Răspunsuri la întrebare
Răspuns de
1
5•53-{4•[5+(a-2)•7]:3}•6=1
5•53-[4•(5+7a-14):3]•6=1
5•53-[(4•(7a-9):3]•6=1
265-[(28a-36):3]•6=1
3•265-(28a-36)•6=3
795-168a+216=3
1008=168a
a=1008:168
a=6
5•53-[4•(5+7a-14):3]•6=1
5•53-[(4•(7a-9):3]•6=1
265-[(28a-36):3]•6=1
3•265-(28a-36)•6=3
795-168a+216=3
1008=168a
a=1008:168
a=6
Alte întrebări interesante
Limba română,
8 ani în urmă
Engleza,
8 ani în urmă
Biologie,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă